New data on the spatial distribution of endemic ground beetles (Coleoptera: Carabidae) from Madeira Island - Boieiro, Mário (2012)
Based on standardised sampling methods covering a large fraction of native forest on Madeira Island, new distribution data is reported for 33 species of endemic ground beetles. Most of these species have been found in new localities and their distribution range is now better known. Dromius angustus alutaceus Wollaston, 1857 was "rediscovered" after more than fifty years since the last known record and two rare Philorhizus species (P. conicipennis (Fauvel, 1905) and P. vieirai Mateu, 1957) were also located. Furthermore, two other arboreal endemics (Olisthopus ericae Wollaston, 1854 and O. maderensis Wollaston, 1854) were recorded from many new localities. This work represents a considerable improvement of the knowledge on the distribution of ground beetle species endemic to Madeira, hence contributing to future management plans targeting the conservation of endemic biota.